Pemanfaatan Vitamin C Alami sebagai Antioksidan pada Tubuh Manusia - Safnowandi, Safnowandi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
Vitamin C is an organic substance needed by the human body in small amounts, to maintain metabolic functions and also acts as an antioxidant for the human body, to ward off free radicals. The design of this research is a literature review of research articles collected by means of computer searches through google schoolar and repository. The search step is to enter the keyword Natural Vitamin C Antioxidant, Dosage and source of intake of vitamin C. Vitamin C or L-ascorbic acid is a water-soluble antioxidant (Aqueous Antioxidant). Vitamin C is part of the body's defense system against reactive oxygen compounds in plasma and cells. Vitamin C deficiency and excess will have an effect on our health. Lemons contain about 85 milligrams of vitamin C, guava has a high vitamin C content of 86 mg/100g, 1 pineapple or a plate of longan fruit (about 100 grams) contains about 80 milligrams of vitamin C, and in a bowl of spinach (about 30 grams) contains 8.5 mg of vitamin C.